Dinamika Kehidupan Sosial dalam Pengembangan Ilmu Pengetahuan dan Teknologi - Bagus Jamroji; Darul Ihsan; Ibnu Abbas (Educational Research Center, 2026)
This study aims to analyze the dynamics of social life in the development of science and technology (IPTEK) through a descriptive qualitative approach based on library research. The advancement of science and technology cannot be separated from its social context, as technological innovation emerges in response to societal needs, values, and structural transformations. Data were collected through documentation techniques from relevant scholarly sources and analyzed using thematic analysis to identify patterns and relationships between social change and technological development. The findings reveal that social life serves both as a foundation and a driving force in shaping the direction of scientific and technological innovation. Conversely, technological advancement significantly transforms social interaction patterns, communication systems, and societal structures in contemporary communities. While these transformations enhance efficiency and expand access to information, they also introduce ethical and social challenges, including value shifts, digital inequality, and increasing individualism. Therefore, the development of science and technology should be guided by a humanistic and value-based approach to ensure that innovation strengthens social cohesion and supports sustainable development. This study highlights the importance of integrating digital literacy, ethical awareness, and social responsibility into technological advancement processes in order to maintain a balance between technological progress and the quality of social life.